Pemberdayaan Perempuan melalui Tim Penggerak Pemberdayaan Kesejahteraan Keluarga (TP PKK) dalam meningkatkan Kualitas Kehidupan menuju Keluarga Sejahtera dimasa Pandemi Covid 19 - Syntia, Rita (Program Studi Pendidikan Sejarah - Universitas Samudra, 2022)
This research was motivated by the low quality of the welfare of the community's family during the COVID-19 pandemic. The purpose of this research is to empower women through a team that drives family welfare empowerment in improving the quality of life towards a prosperous family during the Covid 19 Pandemic. The approach used in this research is participatory which actively involves all research subjects to determine programs that are right on target, practically oriented, empowering and sustainable. The results of the study state that the empowerment of women and housewives as small business actors in Aceh Tamiang requires cooperation from the government and government partners, namely TP PKK which plays a very significant role in addition to the private sector and the community so that it is maximized. This empowerment also focuses on handling their difficulties during the Covid-19 pandemic with digital transformation of production and marketing as well as continuous assistance.